2014
DOI: 10.1038/srep05971
|View full text |Cite
|
Sign up to set email alerts
|

The earliest pigeon fanciers

Abstract: Feral Pigeons have colonised all corners of the Earth, having developed a close association with humans and their activities. The wild ancestor of the Feral Pigeon, the Rock Dove, is a species of rocky habitats, nesting typically on cliff ledges and at the entrance to large caves. This habit would have brought them into close contact with cave-dwelling humans, a relationship usually linked to the development of dwellings in the Neolithic. We show that the association between humans and Rock Doves is an ancient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 33 publications
2
48
1
3
Order By: Relevance
“…Some of these localities attest to the exploitation of non-edible avian products, such as talons of raptors, which seem to have been used as ornamental elements. In addition, new results from Gibraltar sites (Finlayson et al, 2012;Blasco et al, 2014) also indicate the presence of cut marks on avian remains during the Mousterian, confirming that bird processing for feathers and consumption is not as strange as previously thought. Even though solid evidence supports avian consumption, its systematic acquisition is still debated.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Some of these localities attest to the exploitation of non-edible avian products, such as talons of raptors, which seem to have been used as ornamental elements. In addition, new results from Gibraltar sites (Finlayson et al, 2012;Blasco et al, 2014) also indicate the presence of cut marks on avian remains during the Mousterian, confirming that bird processing for feathers and consumption is not as strange as previously thought. Even though solid evidence supports avian consumption, its systematic acquisition is still debated.…”
Section: Introductionsupporting
confidence: 65%
“…Experimental and archaeological studies made on bird and other small game accumulations were taken into account as a reference to identify possible hominid (Laroulandie, 2000(Laroulandie, , 2001(Laroulandie, , 2004(Laroulandie, , 2005Laroulandie et al, 2008;Blasco and Fernandez Peris, 2009;Blasco et al, 2014) and carnivore accumulations within the region. The previous studies of bird accumulations focused on birds of prey as the main accumulator agents: eagle owl (Bochenski et al, 1993;Laroulandie, 2000Laroulandie, , 2002, snowy owl (Baales, 1992;Bochenski, 1997), tawny owl (Bochenski et al, 1993;, longeared owl (Bochenski andTomek, 1994, 1997), peregrine falcon (Laroulandie, 2000(Laroulandie, , 2002, gyrfalcon (Bochenski et al, 1998;Bochenski and Tornberg, 2003), golden eagle (Bochenski et al, , 1999(Bochenski et al, , 2009); imperial eagle , and white-tailed eagle (Mlikovsky, 1996;Bochenski et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…These recent discoveries concerning the regular use of bird resources by Neanderthals support the idea that their cognitive abilities were comparable with those of modern humans (Peresani et al, 2011;Finlayson et al, 2012;Morin and Laroulandie, 2012;Blasco et al, 2014;Romandini et al, 2014;Radov ci c et al, 2015). They add to the list of arguments that permit reconsideration of the cognitive and behavioral capacities of Neanderthals (e.g.…”
Section: Bird Resources In Western Europementioning
confidence: 52%
“…The main goal was to explore more precisely the relationships between Homo and small game in other parts of the Old World prior to the end of the Palaeolithic (e.g. Bochenski et al, 2009;Hockett and Haws, 2009;Lloveras, 2010;Blasco et al, 2011Blasco et al, , 2013Blasco et al, , 2014Lloveras et al, 2011;Cochard et al, 2012;Mallye et al, 2013;Wertz et al, 2015). As foreseen by Stiner and Munro (2002, p. 194): "It seems unlikely that all faunal series to be examined in the future will adhere to the patterns found in the three Mediterranean series", and new results from other regions came to light and gave a more complex overview of human subsistence during the Pleistocene in Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Colonization may have been facilitated by a combination of the great human migrations, expansion of domesticated pigeon populations and the huge expansion of international trade in Africa driven by European imperialism [55][56][57][58][59][60]. This theory has been further supported by research in Thailand, where a genetic bottle neck, analogous to a founder effect, was identified in C. neoformans var.…”
Section: Emergence Of Cryptococcus Neoformans As An Endemic Pathogenmentioning
confidence: 93%